PERAN PGRI DI ERA DIGITAL : Peluang dan Tantangan: - - Mohamad Dedi (SOSIOEDUKASI, 2022)
Entering the current digital era, the development of students is very different from the past. The digital era has brought various positive and negative impacts together. Many cases occur in children who do acts of bullying, become individualists, and are less able to socialize in the community. If not fortified, this condition will be very dangerous for their development in the future. As a professional teacher organization in Indonesia, PGRI is required to play a role in aligning the changing times with character values. Various regulations and intervention programs are implemented for children growing up together with technology and using it for positive things. This article is a study of a systematic review of scientific publications in the last 10 years related to the policy and implementation of the digitalization program by the PGRI organization. The results of the research have provided an overview of the roles and challenges of the PGRI organization in shaping the nation's character in the current of digital era